Forensic application of a rapid one-step tetramethylbenzidine-based test for the presumptive trace detection of bloodstains at the crime scene and in the laboratory - De Vittori, E.; Barni, F.; Lewis, Simon; Antonini, G.; Rapone, C.; Berti, A. (Elsevier BV, 2016)
Bloodstains are a widespread kind of biological evidence at the crime scene and one of the most used reagents for the presumptive identification of blood for forensic purposes is tetramethyl-benzidine. We have introduced and validated the tetramethylbenzidine-based Combur3 Test® E (Roche Diagnostics Corporation, Basel, Switzerland), a colorimetric catalytic test based upon the detection of the peroxidase-like activity of the hemoglobin, due to its high sensitivity, easiness of use and capability to maintain the complete structural and morphological integrity of the bloodstain. Analytical performances related to a forensic use of the test and the suitable applicability to the presumptive detection of bloodstains when extremely diluted, aged, mixed with several substances and deposited over a plethora of substrates was reliably proved. In addition, possible positive interferences of the test chemicals on the subsequent Short Tandem Repeats (STRs) DNA typing analyses, especially in Low-Template DNA (LT DNA) conditions, was evaluated. While the Combur3 Test® E showed the same chemical interference drawbacks as other presumptive tests for blood as for the low specificity, we demonstrated that its format and our suggested protocol of use make it appropriate for the forensic presumptive detection of blood, better performing and much easier to use than other analogous presumptive tests and usually compatible with the following STRs DNA typing analyses.